The Relationship of Obesity to Diabetic Foot Ulcer in Type 2 Diabetes Mellitus Patients - Agus Widyatmoko; Wahyu Iqbal Tawakal Santyasna (Fakultas Kedokteran Universitas Lambung Mangkurat, 2022)
Diabetes mellitus is a group of metabolic diseases, the common finding of which is elevated blood glucose levels, known as hyperglycemia. Severe hyperglycemia causes classic symptoms such as polyuria, polydipsia, and polyphagia and unexplained weight loss. This study used an observational descriptive analytic method with a cross sectional design to 42 respondents of type 2 Diabetes mellitus patients at PKU Muhammadiyah Gamping Hospital. The blood sugar levels, HbA1C, height, weight and incidence of diabetic foot ulcers were recorded. Data analysis used the Chi-Square test to see the relationship between obesity and the incidence of diabetic foot ulcers in patients with type 2 diabetes mellitus. The results of the study on 42 respondents showed that there were 31 Diabetes mellitus patients with diabetic foot ulcers (73.8%) while 11 people (26.2%). There were 21 male patients (50%) and 21 female patients (50%). A total of study subjects with normal Body Mass Index had type 2 diabetes mellitus with complications of diabetic foot ulcers (77.8%.), 13 study subjects with overweight Body Mass Index experienced type 2 diabetes mellitus with complications of diabetic foot ulcers (61.9%.), 11 study subjects with Body Mass Index obese class 1 had type 2 diabetes mellitus with complications of diabetic foot ulcers (91.7%). In patients with type 2 diabetes mellitus without complications of diabetic foot ulcers with normal Body Mass Index, there were 2 people (22.8%.) In patients with type 2 diabetes mellitus without complications of diabetic foot ulcers with Body Mass Index overweight, there were 8 people (38.1%). Then in patients with type 2 diabetes mellitus without complications of diabetic foot ulcers with Body Mass Index obesity class 1 obtained 1 person (8.3%). The Chi-Square test was performed and the p value = 0.166. There is no significant relationship between obesity and the incidence of diabetic foot ulcers in patients with type 2 diabetes mellitus.